Use of Natalizumab in Patients with Active Relapsing-Remitting Multiple Sclerosis in Kuwait - Alroughani, R. (Med Princ Pract, 2013)
OBJECTIVE: To evaluate the outcomes of patients with multiple sclerosis (MS) who were treated with natalizumab in Kuwait. MATERIALS AND METHODS: A retrospective study using the MS registry to identify patients who were treated with natalizumab was conducted. Patients’ demographics, clinical characteristics and treatment parameters were collected at baseline and last follow-up visit. Primary outcome was the proportion of relapse-free patients at the last follow-up while secondary outcomes were the change in the mean annual relapse rate, Expanded Disability Status Scale (EDSS) and the proportion of patients with magnetic resonance imaging (MRI) activity at the last follow-up visit. Forty-four patients were included in the study. RESULTS: Of the 44 patients, 27 (61.4%) were females and the remaining 17 (38.6%) males. Mean age of patients and mean disease duration were 29.05 ± 7.25 and 5.71 ± 3.37 years, respectively. The mean number of natalizumab infusions was 18.14. The proportion of relapse-free patients significantly increased from 11.36 to 90.91% (p < 0.0001). The EDSS significantly improved from 4.76 to 3.15 (p < 0.0001) over the observational period. There was no significant difference between patients with EDSS <3 compared to those with EDSS ≥3 (p < 0.67). The proportion of patients with MRI activity was significantly reduced from 95.5 to 18.2% (p < 0.0001) at their last visit. Six patients discontinued the drug, 5 due to positive JC virus and 1 due to pregnancy. CONCLUSIONS: Natalizumab induced a suppression of disease activity and was responsible for a significant improvement in disability status in highly active MS patients.